Taxation aiming environmental protection: The case of Brazilian Rural Land Tax. (August 2022) - Fendrich, Arthur Nicolaus; Barretto, Alberto; Sparovek, Gerd; Gianetti, Giovani William; da Luz Ferreira, Jaqueline; de Souza Filho, Carlos Frederico Marés; Appy, Bernard; de Guedes, Carlos Mario Guedes; Leitão, Sergio
Abstract: Ensuring the protection of natural vegetation is a complex challenge that demands a mix of policies. In Brazil, conservation on private land relies on large-scale command-and-control instruments and a few Payments for Ecosystem Services schemes, with taxation playing a minimal role for conservation. The Rural Land Tax ( Imposto Territorial Rural, ITR) is a long-established rural tax created to stimulate pasture productivity and promoting social, agricultural, and environmental benefits. Despite the potential for environmental protection, several problems lead to low achievement of ITR's goals. Such problems include low revenue, the difficulty in inspecting declarations, obsolete productivity criteria, and intrinsic environmental distortions. In this work, we analyze current ITR and show that distortions can potentially occur even for properties that adopt deforestation in the Amazon. We also built a spatially explicit model that estimate tax revenue at a property level under different scenarios. Then, we simulate two scenarios: the first corresponds to the existing Law, and the second, to a legal revision we propose to overcome some of its current problems. We found that total tax collection under the current Law should be BRL 5.75 bi per year, almost four times the actual value collected in 2017 (BRL 1.5 bi). The results suggest that the low achievement of goals follows from a large group paying meager tax rates and another group being overpenalized. Results for the proposed revision highlight its inherent potential to address ITR's central challenges, and for a given set of parameters, the revenue under the new formulation could rise to BRL 16.8 bi per year. Our results provide a concrete and science-based alternative for ITR. The application of the proposals of revision we suggest could promote additional environmental protection, consequently strengthening the role of taxation as an instrument for the maintenance of natural vegetation in Brazil. Highlights: We evaluate the potential of a land tax for environmental protection in Brazil. We focus on ITR, a long-established rural tax with several known problems. We use examples to illustrate ITR's current environmental distortions. Our spatial simulation shows that current collection is much lower than expected. We propose consistent and science-based alternatives to address ITR's challenges.